The STAMP Test: A Novel Clinical Test in Diagnosing Achilles Tendon Ruptures. Issue 1 (January 2022) - Porter, Giselle M.; Haupt, Edward T.; Kaplan, Jonathan R.; Charlton, Timothy P.
Category: Ankle Introduction/Purpose: Achilles tendon ruptures are common injuries, and an estimated 20-25% injuries are missed acutely. Chronic and acute Achilles tendon rupture patients typically present with nonspecific complaints and physical exam findings. Commonly used physical exam maneuvers such as the Thompson test have variable sensitivity and reliability for the examiner. The patient with an Achilles tendon rupture will have expected plantar-flexion weakness, however clinical data utilizing plantarflexion weakness to develop a physical exam maneuver is lacking. We propose two new tests with sensitivity and specificity analysis to evaluate this understanding in the clinical setting: the Stand and Maintain Plantarflexion (STAMP) and Tendo-Achilles Rise (TAR) tests. We hypothesize that the STAMP and TAR exams maneuvers will have high sensitivity for diagnosis of acute and chronic Achilles tendon rupture. Methods: Data was collected from a single surgeon's practice at two large urban treatment centers. Data was retrospectively acquired over a period of 7 years and then prospectively acquired over a period of 5 years. Patients with mid-substance Achilles tendon rupture confirmed with MRI imaging or operative treatment were included. We examined clinical data regarding ambulation, resting tension, palpable Achilles gap, Thompson test, and STAMP and TAR tests on initial presentation. The STAMP test is performed by the patient attempting a wall assisted double leg heel rise and lifting the uninjured foot off the ground. It is consistent with an Achilles tendon rupture if the patient is unable to maintain this position for five seconds. The TAR test is performed by the patient attempting a wall assisted single leg heel rise. It is consistent with an Achilles tendon rupture if the patient is unable to maintain this position for five seconds. Results: 71 patients with complete mid-substance Achilles tendon ruptures that met inclusion criteria were identified. 45 (63%) presented acutely and 26 patients (37%) presented chronically. The Thompson test displayed a diagnostic sensitivity of (12 26 46%) for chronic ruptures and (38 45 84%) for acute ruptures. The STAMP and TAR tests displayed a diagnostic sensitivity of (22 26 85%) for chronic ruptures and (45 45 100%) for acute ruptures with a diagnostic specificity of (89%). Conclusion: Achilles tendon ruptures can be difficult to diagnose due to inconsistent symptoms and clinical exam findings. The STAMP and TAR physical exam tests have high sensitivity to clinically diagnose Achilles tendon rupture both in the acute and chronic setting and are superior to well-described physical exam tests. The findings support that the addition of the STAMP and TAR diagnostic protocol may be clinically beneficial when diagnosing Achilles tendon ruptures in both the acute and chronic setting. Future work should be focused on providing direct comparison to other exam maneuvers as well as identifying data reliability.